The Role of Financial Technology (FinTech) and Sustainable Economic Growth: Emerging Digital Solutions in Oman (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study examines the growing influence of financial technology (FinTech) on sustainable economic growth in Oman, with a focus on how digital financial solutions support the country’s transition toward a more resilient and innovation driven economy. The research explores key FinTech developments, including mobile payment systems, digital banking platforms, blockchain applications, and automated financial services and evaluates their contribution to financial inclusion, operational efficiency, and environmentally responsible economic activities. Using a mixed-method approach, the study analyzes policy initiatives, market trends, and stakeholder perspectives to assess the effectiveness of FinTech in advancing national sustainability objectives outlined in Oman Vision 2040. The findings indicate that FinTech plays a critical role in strengthening SME financing, promoting green investment, and enhancing transparency in financial transactions. The study concludes that continued expansion of digital infrastructure, regulatory support, and public–private collaboration is essential for maximizing the long-term economic and environmental benefits of FinTech in Oman.